BRCA-Associated Ovarian Cancer: From Molecular Genetics to Risk Management. (22nd July 2014) - Girolimetti, Giulia; Perrone, Anna Myriam; Santini, Donatella; Barbieri, Elena; Guerra, Flora; Ferrari, Simona; Zamagni, Claudio; De Iaco, Pierandrea; Gasparre, Giuseppe; Turchetti, Daniela
Abstract : Ovarian cancer (OC) mostly arises sporadically, but a fraction of cases are associated with mutations in BRCA1 and BRCA2 genes. The presence of a BRCA mutation in OC patients has been suggested as a prognostic and predictive factor. In addition, the identification of asymptomatic carriers of such mutations offers an unprecedented opportunity for OC prevention. This review is aimed at exploring the current knowledge on epidemiological and molecular aspects of BRCA-associated OC predisposition, on pathology and clinical behavior of OC occurring in BRCA mutation carriers, and on the available options for managing asymptomatic carriers.